Reliabilitas Kendaraan Listrik - Silvi Istiqomah; Perdana Suteja Putra; Rizqa Amelia Zunaidi; Rizha Nurmila Hilda (CV. Multi Kreasi Media, 2023)
The global transition towards sustainable transportation solutions has spurred the rapid growth of electric vehicles (EVs) as a promising alternative to traditional internal combustion engine vehicles. However, as the adoption of EVs continues to accelerate, the focus has shifted towards ensuring the longevity of electric vehicle operations worldwide. This study aims to provide an in-depth exploration of the multifaceted aspects surrounding the longevity of EV operations on a global scale. The longevity of electric vehicle operations encompasses various dimensions, including technological advancements, infrastructure development, policy support, and consumer behavior. Firstly, advancements in battery technology play a pivotal role in determining the lifespan of EVs. The article delves into the evolution of battery chemistries, energy densities, and thermal management systems, which collectively impact battery life and overall vehicle longevity. Additionally, insights into battery recycling and second-life applications are discussed as essential strategies to mitigate environmental impacts and enhance the sustainability of EV operations.